A catalogue of training and extension materials on Integrated Pest Management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Integrated Pest Management; a catalogue of training and extension materials for projects in tropical and subtropical regions' by FAN van Alebeek, 1989, 305 pages, available from CTA.